2015
DOI: 10.1007/s13277-015-3377-3
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated TRIO expression correlates with a malignant phenotype in human hepatocellular carcinoma

Abstract: Triple functional domain protein (TRIO) is an evolutionarily conserved Dbl family guanine nucleotide exchange factors (GEFs) involved in cell proliferation and progression of some types of cancer. However, the expression and prognostic role of TRIO in hepatocellular carcinoma (HCC) have not yet been determined. Therefore, we attempted to determine the impact of TRIO on the clinical outcome of HCC patients to further identify its role in HCC. TRIO expression was examined using quantitative real-time PCR (qRT-PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Rho-GTPase proteins participate in cell motility and actin cytoskeleton reorganization (18). RhoA is a member of the Rho-GTPase proteins and acts as a switch between the active GTP-bound form and inactive GDP-bound form.…”
Section: Knockdown Of Trio By Crispr/cas9 Inhibits Cervical Cancer Cementioning
confidence: 99%
See 2 more Smart Citations
“…Rho-GTPase proteins participate in cell motility and actin cytoskeleton reorganization (18). RhoA is a member of the Rho-GTPase proteins and acts as a switch between the active GTP-bound form and inactive GDP-bound form.…”
Section: Knockdown Of Trio By Crispr/cas9 Inhibits Cervical Cancer Cementioning
confidence: 99%
“…Since Trio controls a wide range of cellular processes, dysregulation of its activity is related to the emergence of diseases. Trio was demonstrated to be highly upregulated in urinary bladder tumors (11), soft tissue sarcomas (12), breast cancer (13), and various other types of cancer (11)(12)(13)(14)(15)(16)(17)(18)(19). Higher Trio levels were closely related to invasive tumor phenotype, high tumor grade, and rapid tumor cell proliferation in breast tumors (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should however be noted that only 4/25 cancer samples were characterized as CCC. TRIO plays a role in cell proliferation and progression of cancer, wherein higher protein expression has been shown to be associated with worse outcome (OS) (44). To the best of our knowledge, we are the first to report an association between CCC-related biomarkers (ARPC2, CCT5, GNB1, KCTD10, NUP155, RPL13A, RPL37, SETD3, SMYD2, TRIO) and prognosis.…”
Section: Discussionmentioning
confidence: 89%
“…TRIO was also recently implicated in the invasion process in colorectal and hepatocellular carcinoma. 29,30 But while it was recently reported that AKT phosphorylates TIAM1 and thereby increases its stability, 31 nothing is currently known about the regulation of TRIO by AKT. Very recently, Marcos-Ramiro and colleagues also reported a relationship between RHOB and RAC1 in the endothelium, where RHOB was shown to negatively regulate RAC1 activity and trafficking at endosomes after injury, resulting in the inhibition of barrier recovery after acute contraction.…”
Section: Rhob Downregulation Activates the Akt1-trio-rac1 Signaling Amentioning
confidence: 99%